Police superintendent and schizophrenia : developing sustainable (self) as read in a tale of sustainable development - Virtanen, Akseli (Working papers / Helsingin kauppakorkeakoulu, ISSN 1235-5674, 1995)
Tiivistelmä: Poliisiylipäällikkö ja skitsofrenia.
Keywords: semiotiikka; Organization; Semiotics; Environmental policy; organisaatiot; organisaatiokulttuuri; ympäristöpolitiikka; utvecklingsfilosofi